Analyzing financial performance of commercial banks in India: Application of CAMEL model - Mohi-ud-Din Sangmi; Tabassum Nazir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Sound financial health of a bank is the guarantee not only to its depositors but is equally significant for the shareholders, employees and whole economy as well. As a sequel to this maxim, efforts have been made from time to time, to measure the financial position of each bank and manage it efficiently and effectively. In this paper, an effort has been made to evaluate the financial performance of the two major banks operating in northern India .This evaluation has been done by using CAMEL Parameters, the latest model of financial analysis. Through this model, it is highlighted that the position of the banks under study is sound and satisfactory so far as their capital adequacy, asset quality, Management capability and liquidity is concerned.
Keywords: 330; financial performance; commercial banks; capital Adequacy; asset quality; management capability; earnings analysis; liquidity analysis